2021
DOI: 10.3390/atmos13010074
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Ground-Based Microwave Radiometer on Heavy Rainfall Forecast in Beijing

Abstract: Ground-based microwave radiometers (MWRPS) can provide continuous atmospheric temperature and relative humidity profiles for a weather prediction model. We investigated the impact of assimilation of ground-based microwave radiometers based on the rapid-refresh multiscale analysis and prediction system-short term (RMAPS-ST). In this study, five MWRP-retrieved profiles were assimilated for the precipitation enhancement that occurred in Beijing on 21 May 2020. To evaluate the influence of their assimilation, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…When utilized for Numerical Weather Prediction (NWP), MWR soundings have been found to exhibit accuracy on par with radiosonde soundings [49]. Several studies incorporating MWR retrieval profiles have demonstrated their potential in enhancing the forecast of local weather phenomena [50][51][52][53][54]. The RPG-HATPRO MWR system consists of 14 channels, which are divided into seven K-band channels for water vapor profile retrieval and seven V-band channels (oxygen band) for temperature profile retrieval.…”
Section: Agri Radiance and Mwr Datamentioning
confidence: 99%
See 1 more Smart Citation
“…When utilized for Numerical Weather Prediction (NWP), MWR soundings have been found to exhibit accuracy on par with radiosonde soundings [49]. Several studies incorporating MWR retrieval profiles have demonstrated their potential in enhancing the forecast of local weather phenomena [50][51][52][53][54]. The RPG-HATPRO MWR system consists of 14 channels, which are divided into seven K-band channels for water vapor profile retrieval and seven V-band channels (oxygen band) for temperature profile retrieval.…”
Section: Agri Radiance and Mwr Datamentioning
confidence: 99%
“…Hence, the assimilation of MWR data can enhance weather forecasts of NWP models. For instance, a case study was conducted in Beijing to assess heavy rainfall by assimilating data from seven ground-based MWRs using 3-Dimensional Variational Assimilation (3DVAR) [38]. Nevertheless, MWR's utilization remains insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, when the sun is in the observation direction of the MWR, the BT data will be abnormally increased due to the influence of solar radiation, especially those used in low latitudes [14]. Therefore, it is essential to control the quality of the MWR observation data for a better forecast [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…As a new type of atmospheric microwave remote sensing detection equipment, MWR has the advantages of long-term continuous observation, low equipment maintenance cost and high path resolution in the troposphere. It is the most ideal detection equipment for measuring cloud liquid water and water vapor density at this stage [2,3]. MWR inversion of temperature and humidity profile algorithm is mainly divided into physical inversion method and statistical inversion method.…”
Section: Introductionmentioning
confidence: 99%